Pengaruh Sosial Ekonomi Orang Tua Dan Potensi Diri Terhadap Minat Siswa Melanjutkan Ke Perguruan Tinggi - Natasya Azzahra; Aditya Pratama; Riswandi Riswandi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine the influence of parents' socio-economic status on students' interest in continuing to higher education, with self-potential as a mediating variable. This is a quantitative study with an explanatory approach. The population and sample size were 76 12th-grade students of SMA Negeri 79 Jakarta majoring in economics. The data were processed and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0. The results of this study indicate that (1) There is a significant influence between the socio-economic status of parents on students' interest in continuing to college (2) There is a significant influence between the socio-economic status of parents on self-potential (3) There is a significant influence between self-potential on students' interest in continuing to college (4) There is a significant influence between the socio-economic status of parents on students' interest in continuing to college through self-potential.